(untitled) (Web of Teachers: Inderscience Research, 2024)
In today’s interconnected world, critical thinking has become a cornerstone of effective communication and problem-solving. English language learning, beyond its linguistic benefits, provides a unique platform for cultivating critical thinking skills. This article explores the integration of critical thinking activities in English language classrooms and their impact on learners’ overall cognitive development.